Conductive cooling of the forehead during exercise attenuates a rise in core temperature - Carrasco, M.A. (Science & Sports, 2013)
The purpose of this study was to determine if conductive cooling of the forehead during exercise can attenuate a rise in core temperature. Subjects cycled indoors at 65% maximum power output (Wmax) to volitional fatigue on cycle ergometers once with cooling and once without. Forehead cooling resulted in attenuation of the rise in TCORE (P < 0.05). The mean sweat loss for the CON treatment was higher than the COOL, 2887.50, sx- = 531.52 mL and 2007.50, sx- = 365.86, respectively (P = 0.01). Mean heart rate was lower in the COOL treatment than the CON by 11-22 bpm-1 at all time points.